"This is a patriotism check": Political economy, corruption, and duty to America in the 2020 primary debates. (2nd October 2021) - Coker, Calvin R.; Reed, Joel L.
Abstract: The 2020 Democratic presidential primaries involved the largest and most diverse slate of candidates in the modern era of party nominee selection, a diversity that allowed some candidates to reject neoliberal discourses endemic to American politics. In this essay, we analyze the 2020 Democratic primary debates to demonstrate the emergence of an alternative political economy that stands in opposition to standard economic orthodoxy. Candidates organized their critiques of the extant political economy around corruption, presenting it as rot at the heart of the present capitalist order, with Donald Trump more symptom than cause of America's unjust and deeply flawed economic system. That rot compelled candidates to present an alternative in "economic patriotism" which posited obligation to the collective above and in opposition to neoliberal profit. The essay concludes by unpacking the implications of this break from orthodoxy in the campaign debate context.